Chaid And Anova Analysis On The Factors Of Impulsive And Compulsive Buying Behavior – A Comparative Study (Journal of Namibian Studies : History Politics Culture, 2023)
This paper presents a comprehensive review and comparison of impulsive and compulsive buying behavior, two distinct but related phenomena in consumer psychology. Impulsive buying refers to spontaneous and unplanned purchases driven by immediate emotional or situational triggers, while compulsive buying involves repetitive and excessive purchasing behaviors characterized by an irresistible urge to buy, often leading to negative consequences. The aim of this review is to analyze the similarities and differences between impulsive and compulsive buying behavior, examining their underlying psychological mechanisms, triggering factors, and consequences. By understanding these distinct consumer behaviors, marketers, psychologists, and policymakers can develop effective strategies to address their impact on individuals and society. Commonalities between the two behaviors include the role of emotions, cognitive factors, and environmental cues in stimulating buying urges. Furthermore, this review discusses the psychological, social, and financial consequences associated with both behaviors. Impulsive buying may lead to immediate gratification but can also result in regret, financial strain, and reduced well-being. In contrast, compulsive buying is often associated with deeper psychological issues, such as low self-esteem, anxiety, and compulsive hoarding. The implications of these findings extend beyond individual consumer behavior. Businesses can utilize this knowledge to tailor marketing strategies that appeal to impulsive or compulsive buyers, while also implementing responsible selling practices. Moreover, healthcare professionals and psychologists can develop targeted interventions and therapies to help individuals struggling with these buying behaviors, fostering healthier consumption habits and overall well-being. In conclusion, this review highlights the distinct characteristics of impulsive and compulsive buying behavior, providing a foundation for further research and practical interventions. By gaining a deeper understanding of these consumer tendencies, stakeholders can work towards minimizing the negative impacts of impulsive and compulsive buying while promoting mindful and responsible consumption patterns.